EFFECTS OF WAI KHRU MUAYTHAI TRAINING TO BALANCE ABILITY IN THE ELDERLY - Yanyong Phanpheng; Warayot Larha; Ashira Hirantrakul (Sport Scientific And Practical Aspects, 2025)
The objectives of this quasi-experimental research were to study the effects of Wai Khru muaythai to balance ability in the elderly. The 56 elderly participants attending the health promotion project in a school for the old people in Loei province, Thailand, aged 60-75 years old, with similar physical conditions including age, weight, height and IBM. The samples were purposively selected based on the specific criteria. There were 2 experimental groups; 28 participants training for Wai Khru muaythai (WMT) and control group 28 subjects walking for exercise. The details of exercise activity were added as a part of health promotion activity for the school for the old people. The training took 12 weeks, 3 times a week, and 30 minutes for each training activity. Both groups were tested for the physical and balance ability with Functional reach test (FRT), dynamic balance with Timed Up and Go Test (TUG) and strength and endurance of muscular using 30 Second Chair Stand (CST) before and after training. The data was analyzed by Paired Sample t-test and Independent t-test at significant level at 0.05. The results of the study showed that both experimental groups had physiological statistical significance and balance ability which increase when testing by FRT and CST comparing the control group p<0.05. While testing TUG, the period of time reduced in both groups. It can be seen that Wai Khru muaythai, can increase strength of lower body which are the factors enhancing the balance ability which is the basic of movement.